INDIAN INSTRUMENT MAKERS IN PERFORMING ARTS - Sukanya Sarker (Arts Academy)
The currently popular Indian Musical Instruments have undergone tremendous changes during the passing of time. This has occurred in terms of its playing styles, modes of presentations and its architecture. What caused these changes is remained to be studied. There might be some inter-relationship between these four factors, namely, the changes/advancement occurred in playing techniques, picking preferences of playable materials, changes in execution styles and the changes of architecture of the instruments. Consequently, the effect of changes in the society which directly reflected on the patronization and general attitude of the people towards this art form may have played important roles in the changes in music. How the musicians felt the urge of widening its area of penetration amongst the masses of the world and what was the impact of globalization on this art and craft remained to be studied.